Effect of composting of palm oil mill wastes and organic manure on tomato (Lycopersicon esculentum Mill.) growth and yield - KOURA, Tatiana W.; DAGBENONBAKIN, Gustave D.; KINDOMIHOU, M. VALENTIN; SINSIN, Brice (My University, 2015)
Compost made of palm oil empty fruit bunches, fibre, poultry manure and cattle dung composted in shelter were applied to tomato [Lycopersicon esculentum (Mill.)] to evaluate their effects on its growth and yield. The trials consisted in a split-split plot design with two levels of composting method (without cover or under cover) and the types (no manure, poultry manure, cow dung) and rates of compost application (0t/ha, 5t/ha, 10t/ha, 20t/ha) as secondary factors. The height and stem girth of three plants per plot were measured weekly at 6 weeks after transplanting. The total number of fruits, marketable fruits and fruit weights were collected at production phase. All data collected from the tree trials were put together and the analysis were made with four ways ANOVA with repeated measured to determine if there were significant differences amongst treatments. There were no significant effects between the compost made under cover and those made in the open on tomato plant height at 6 weeks after planting. There was no significant effect of composting method, type of manure and compost rate application on Lycopersicon esculentum. The effect of compost application on tomato yields was significant at 10t/ha compost application rate. The total number of tomatoes fruits depended significantly (p<0.05) on the compost application rate. The highest number of tomatoes fruits obtained was 19.4 at 20t/ha as compost application rate.
Keywords: Aricsol; Compost; Manure; Palm oil mill wastes; Tomato